2017
DOI: 10.15226/sojmid/5/4/00179
|View full text |Cite
|
Sign up to set email alerts
|

Does Land Cover Influence the Spatial Distribution of Reservoir Rodent Necromys Lasiurus?

Abstract: The rodent Necromys lasiurus (Rodentia, Sigmodontinae) is considered to be the main hantavirus reservoir in the Brazilian Cerrado biome. Significant changes to the landscape of this biome have occurred in recent decades. Considering the fact that change in land use patterns can influence species distribution and, as a result, the emergence of diseases, this study sought to analyze the potential geographic distribution of the species N. lasiurus and to understand how land use and occupation contribute to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In Amazonia, the species is found in savanna vegetation (Ghizoni et al, 2005) and in the Atlantic Forest it is often found in agroecosystems (Gheler-Costa et al, 2012). Santos et al (2018) and Malange et al (2016) noted that crops and pastures have favored the expansion of the species in the Atlantic Forest, and human-modified environments are associated with the occurrence of the species in all Brazilian domains (Santos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Amazonia, the species is found in savanna vegetation (Ghizoni et al, 2005) and in the Atlantic Forest it is often found in agroecosystems (Gheler-Costa et al, 2012). Santos et al (2018) and Malange et al (2016) noted that crops and pastures have favored the expansion of the species in the Atlantic Forest, and human-modified environments are associated with the occurrence of the species in all Brazilian domains (Santos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Necromys lasiurus is considered to be one of the main hantavirus reservoirs in Brazil (Oliveira et al, 2013;Santos et al, 2017), and hence surveillance of its populations is of important. This species shows abrupt density fluctuations, and changes from extremely common to rare between seasons or years (Souza and Alho, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Os registros de presença do P. scutatus foram delimitados, considerando o local exato e/ou centróide do município de sua ocorrência. Através da ferramenta Google Earth, foram coletados os pontos em coordenadas geográficas (latitude/longitude), no formato de graus decimais, Datum WGS-84 (OLIVEIRA et al, 2015;SANTOS et al, 2017).…”
Section: Methodsunclassified
“…Among several predictive models, the MaxEnt (Maximum Entropy) algorithm allows to correlate the species occurrence to bioclimatic variables, and predict areas of environmental suitability for the species , Soberón 2007, Philips & Dudik 2008, Olivero et al 2016. It is also possible to insert environmental variables in the prediction, such as topography, forest vegetation (Rajão et al 2010, Oliveira et al 2015 and land use (Santos et al 2017).…”
Section: Introductionmentioning
confidence: 99%